Perbedaan Kematangan Sosial Anak Usia Dini Ditinjau Dari Keikutsertaan Di Taman Penitipan Anak (TPA) - Adinni Vibrananda Lisardika; Heru Astikasari Setya Murti (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2017)
This research aims to know the defferent between social maturity early childhood In terms of participation in Children Day-Care. Sample in this research 60 subject consisting of 30 kids the age of 2 - 6 years charity at Children Day-Care and 30 kids the age of 2 - 6 years who do not charity at Children Day-Care. Technique the sample used in this research was sampling purposive. A measuring instrument used in this researchwas vineland social of maturity scale (VSMS). This research in analysis by using test t (t-test) and obtained value of 10,037 uji-t and shows that significance obtained 0,000 (p < 0,001).The results of this means that there is a significant difference between ripeness child social is 1,093 and those who did not were entrusted in Children DayCare. Most of the dependants were in the landfill is considered to be in the category of ripeness of high social with rerata 108,3, while the majority of children who are not sent to the landfill was ripeness into the category of a social enough with rerata 82,18.Keyword : Social Maturity, Childhood, Children Day-Care